Experimental Evaluation of Anion Exchange Membranes for the Desalination of (Waste) Water Produced after Polymer-Flooding - Paulina A. Sosa-Fernández; Jan W. Post; Harrison L. Nabaala; Harry Bruning; Huub Rijnaarts (Membranes, 2020)
Electrodialysis (ED) has been recently proposed to desalinate polymer-flooding produced water (PFPW), a byproduct stream from the oil and gas industry rich in charged polymers. However, process performance is limited by fouling occurring on the ion-exchange membranes, particularly on the anionic ones (AEMs). Thus, this study aimed to correlate the properties of different AEMs with their performance while desalinating PFPW, ultimately evaluating their significance when fouling is to be minimized and operation improved. Six stacks containing different homogeneous and commercially available AEMs were employed to desalinate synthetic PFPW during 8-days ED experiments operated in reversal mode. AEMs recovered from the stacks were analyzed in terms of water uptake, ion-exchange capacity, permselectivity, and area resistance, and compared with virgin AEMs. Relatively small changes were measured for most of the parameters evaluated. For most AEMs, the water uptake and resistance increased, while the ion-exchange capacity (IEC) and permselectivity decreased during operation. Ultimately, AEMs with high area resistance were linked to the fast development of limiting current conditions in the stack, so this property turned out to be the most relevant when desalinating PFPW.